Plasma concentrations of levobupivacaine in neonates during caudal epidural analgesia maintained over 48 hours - Šípek, Jan; Pokorná, Pavla; Šíma, Martin; Berka, Ivan; Hložek, Tomáš; Stýblová, Jitka; Mixa, Vladimír; Nedomová, Barbora (Bratislavské lekárske listy, 2023)
Abstract: BACKGROUND: Differences in neonatal pharmacokinetics are known to cause systemic accumulation of levobupivacaine with adverse effects during epidural analgesia. Therefore, it is not recommended to surpass 48 hours of administration in neonates. Free and total levobupivacaine levels are considered as predictors of toxicity. OBJECTIVE: The aim of the LEVON pilot study was to detect the accumulation of levobupivacaine during epidural analgesia exceeding 48 hours in neonates. METHODS: Ten neonates received a loading dose of levobupivacaine (1.25 mg/kg) followed by a continuous infusion (0.2 mg/kg/hour) epidurally. Free and total levobupivacaine concentrations were measured 0.5, 1, 6, 12, 36, 72 and 144 hours after the start of infusion. Cumulative doses of levobupivacaine, pain scores and clinical signs of toxicity were used for assessing efficacy and safety. RESULTS: The median concentrations of total levobupivacaine were 586.0, 563.0, 837.5, 957.0, 1930.0, 708.5 and 357.5 ng/ml. The median concentrations of free levobupivacaine were 4.0, 3.6, 5.5, 3.6, 5.5, 0.8 and 0.0 ng/ml. Three patients reached concerning concentrations of total levobupivacaine. Levels of free levobupivacaine remained low. No signs of toxicity were observed. CONCLUSION: Caudal epidural analgesia with levobupivacaine lasting longer than 48 hours appears to be safe providing that free levobupivacaine levels are below the presumed threshold for toxicity (Tab. 1, Fig. 1, Ref. 29).